Illegality and Identity: The Complex Belonging of Undocumented Indonesian Migrants in Amsterdam - Mahshushah (Lembaran Antropologi, 2024)
This study explores the experiences of undocumented Indonesian migrant workers in Amsterdam, the Netherlands, with a specific focus on their sense of belonging within the host society. Undocumented status profoundly shapes their experiences, creating layers of vulnerability and marginalization that compel reliance on informal networks for survival and emotional well-being. Through 33 in-depth interviews and participant observations, this research adopts a subject-centered approach to investigate how undocumented migrants perceive and experience belonging. The analysis prioritizes their perspectives, identifying two key factors—social networks and cultural familiarity—that influence their sense of belonging. Social networks within the Indonesian community play a central role, providing critical support in areas such as housing, employment, and emotional well-being. These trusted connections, often formed through community groups and organizations, help migrants navigate life under restrictive conditions while avoiding detection. Cultural practices, such as enjoying Indonesian cuisine, participating in religious observances, and engaging in community events, further sustain their identity and create spaces of solidarity. Despite prolonged stays, particularly among 11 participants who have resided in Amsterdam for seven years or more, these migrants do not develop a strong sense of belonging to the Netherlands. Instead, their sense of belonging remains deeply tied to Indonesia, reflecting the interplay between legal precarity, social connections, and cultural identity. This study highlights how undocumented status influences these dynamics, offering a fresh perspective on the resilience of marginalized communities in crafting belonging under conditions of exclusion.